ASTEROIDS SEARCH RESULTS IN DIGITIZED OBSERVATIONS OF THE NORTHERN SKY SURVEY PROJECT (KITAB PART) - Shatokhina, S. V.; Relke, H.; Yuldoshev, Q.; Andruk, V. M.; Protsyuk, Yu. I.; Muminov, M. (Одеські астрономічні публікації, 2018)
Photographic observations of XX century contained numerous and varied information about all objects and events of the Universe fixed on the astronegatives. The original and interesting observations of small bodies of the Solar system in previous years can be selected and used for various scientific tasks. Existing databases and online services can help make such selection easily and quickly. The observations of chronologically earlier oppositions, photometric evaluation of brightness for long periods of time allow refining the orbits of asteroids and identifying various non-stationarities. Photographic observations of the Northern Sky Survey project were used for global search for small bodies of Solar system. About 2,000 photographic plates of Kitab part of the Northern Sky Survey project were made using Double Wide Angle Astrograph at the Kitab observatory, Uzbekistan during 1981-1989. Early, using that digitized observations the catalogue of equatorial coordinates and stellar magnitudes for 13 413 268 stars and galaxies up B≤17.5m was composed. At present, we analyzed all processing results for the search of asteroids and compilation of the catalogue of equatorial coordinates and stellar magnitudes of them. As a result more than 4,500 asteroids and comets with visual magnitude from 7m.7 to 17m.5 were identified now. All positions of asteroids were compared with ephemeris. A comparative analysis of O-C differences was carried out. New and interesting is that the moments of discovery of some identified asteroids much later than their moments of observation. In addition, some of them are the earliest observations of these asteroids in the world among all known observations. More than 915 observations of such asteroids have been found on the plates of Kitab part of the FON project.